Hi Guys,

This is regarding the post I was going through..

My question is

statement 1+2 gives us

x4/2 = x4/(x4+1)

here we are equating x4+1=2 => x4=1

why dont we cross multiply here which gives us x4=0 or 1?

original post:

Question: Given x1, x2, x3, ...; What is x1?

...(1) Xi = Xi-1/2

e.g. X2 = X1/2, X3 = X2/2

No number to find x1. INSUFF

...(2) x5 = x4/(x4 + 1)

No number to find x1. INSUFF

...(1) + (2);

Now we know the format Xi = Xi-1/2

and X5 = X4/(X4+1)

Clearly, X4 + 1 = 2

X4 = 2-1 = 1

X4 = (X3)/2 = 1; X3 = 2

X3 = (X2)/2 = 2; X2 = 4

..Keep going and you will know X1. Thus, (1) + (2) SUFF.